Enzymatic and Functional Analysis of a Protein Phosphatase, Pph3, from Myxococcus xanthus - Kimura, Yoshio (American Society for Microbiology, 2011)

(untitled)
A protein phosphatase, designated Pph3, from Myxococcus xanthus showed the enzymatic characteristics of PP2C-type serine/threonine protein phosphatases, which are metal ion-dependent, okadaic acid-insensitive protein phosphatases. The pph3 mutant under starvation conditions formed immature fruiting bodies and reduced sporulation.